Post-Traumatic Stress Disorder among the Flood Affected Population in Indian Subcontinent - Asim, Mohammad; Mekkodathil, Ahammed; Sathian, Brijesh; Elayedath, Rajesh; N, Rajeev Kumar; Simkhada, Padam; van Teijlingen, Edwin (Nepal Journal of Epidemiology, 2019)
Globally, frequent flooding causes higher magnitude of disaster among the developing and developed nations. Particularly, the Indian subcontinent is considered as highly vulnerable area for natural disaster and is affected most because of limited resources and coping strategies for post-disaster rehabilitation. Apart from the great impact on human health, floods have considerable impact on mental health. The most frequently diagnosed psychological illness in flood affected population is post-traumatic stress disorder (PTSD). In India, the incidence of PTSD in major natural disasters varies considerably depending upon the magnitude of event, with the highest rates reported of around 70%. Studies conducted during initial few months post-disaster, showed a higher occurrence of psychiatric manifestations. On the other hand, some reports suggested contrary results under similar circumstances. Notably, extreme age (children and elderly), female gender, socioeconomic status, pre-existing mental health issues and financial crisis post-disaster are the potential predisposing factors influencing the vulnerability of PTSD. In Indian context, the variability in the magnitude of psychiatric illness is mainly attributed to the ethnic diversity (vulnerable population), severity and type of flood event and social support. Still there is more to explore regarding the long-term sequelae of catastrophic floods on physical and mental trauma on disaster-affected populations.